A disintegrin and metalloproteinase 8 induced epithelial‐mesenchymal transition to promote the invasion of colon cancer cells via TGF‐β/Smad2/3 signalling pathway. Issue 22 (20th September 2020) - Jin, Qianna; Jin, Xin; Liu, Tao; Lu, Xiaoming; Wang, Guobin; He, Nan
Abstract: A disintegrin and metalloproteinase 8 (ADAM8) protein is a multi‐domain transmembrane glycoprotein which involves in extracellular matrix remodelling, cell adhesion, invasion and migration. ADAM8 and epithelial‐mesenchymal transition (EMT) play an important role in tumour invasion has been well established. However, the interaction between ADAM8 and EMT has remained unclear. The data of colon cancer patients obtained from TCGA (The Cancer Genome Atlas) and GTEx (Genotype‐Tissue Expression Project) were analysed by the bioinformatics research method. The expression of ADAM8 in colon cancer cells was up‐regulated and down‐regulated by transfecting with the expression plasmid and small interfering RNA, respectively. Transwell invasion assay, immunohistochemistry, immunocytochemistry, Western blotting and qRT‐PCR were utilized to study the effect of ADAM8 on colon cancer cell's EMT and its related mechanisms. Analysis of TCGA and GTEx data revealed that ADAM8 was linked to poor overall survival in colon cancer patients. Besides, ADAM8 was correlated with multiple EMT biomarkers (E‐cadherin, N‐cadherin, Vimentin, Snail2 and ZEB2). In vitro, we also proved that the up‐regulation of ADAM8 could promote EMT effect and enhance the invasive ability of colon cancer cells. On the contrary, the down‐regulation of ADAM8 in colon cancer cells attenuated these effects above. Further studies suggested that ADAM8 modulated EMT on colon cancer cells through TGF‐β/Smad2/3 signalling pathway. Our research suggested that ADAM8 could be a potential biomarker for the prognosis of colon cancer and induced EMT to promote the invasion of colon cancer cells via activating TGF‐β/Smad2/3 signalling pathway.